Perceived stress among physiotherapy and law students at UNEC - Nanuque Campus: A comparative study (International Seven Journal of Health Research, 2023)
Introduction: Stress is the result of a set of disorders that occur on a daily basis, causing an irregularity in the individual's homeostasis. Entering the academic environment brings with it various divergent situations that can culminate in a possible appearance or increase in stress, bringing changes in the emotional state due to the more intense pace of life, learning difficulties, and a decline in academic performance. Aim: To carry out a comparative study on perceived stress among Physiotherapy and Law students at the Centro Universitário de Caratinga (UNEC) - Nanuque Campus. Methodology: This is a quantitative, exploratory and descriptive study, in which the presence of stress was studied and analyzed among Physiotherapy and Law students from the 1st and 9th periods enrolled at the UNEC - Nanuque Campus, using a structured and validated questionnaire that assessed the students' level of stress. Results: Composed of 107 students from the Physiotherapy and Law courses from the 1st and 9th periods, the sample identified that in both courses more than 50% of the students showed medium stress, the Physiotherapy course showed higher levels of stress than the Law course and when compared by gender between the courses, women showed a higher level of stress than men. Conclusion: The study highlighted the possible reasons for increased stress in students, showing that it can negatively affect some aspects of social and academic life, and that attitudes are needed to minimize damage and possible stressors.